2008
DOI: 10.1002/adfm.200800865
|View full text |Cite
|
Sign up to set email alerts
|

Sensing of Damage Mechanisms in Fiber‐Reinforced Composites under Cyclic Loading using Carbon Nanotubes

Abstract: The expanded use of advanced fiber‐reinforced composites in structural applications has brought attention to the need to monitor the health of these structures. It has been established that adding carbon nanotubes to fiber‐reinforced composites is a promising way to detect the formation of microscale damage. Because carbon nanotubes are three orders of magnitude smaller than traditional advanced fibers, it is possible for nanotubes to form an electrically conductive network in the polymer matrix surrounding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
113
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(114 citation statements)
references
References 28 publications
1
113
0
Order By: Relevance
“…Most of the research efforts to date have either been directed towards: 1) CNT based elements/patches [6] for external sensing and; 2) CNT based polymer nanocomposites and CNT based composites having CNT networks distributed throughout the bulk of the material [7][8][9][10][11]. In addition to these two well established research areas, more recent studies have been conducted on CNT based yarns [12] and CNT based sheets [13] for strain sensing.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the research efforts to date have either been directed towards: 1) CNT based elements/patches [6] for external sensing and; 2) CNT based polymer nanocomposites and CNT based composites having CNT networks distributed throughout the bulk of the material [7][8][9][10][11]. In addition to these two well established research areas, more recent studies have been conducted on CNT based yarns [12] and CNT based sheets [13] for strain sensing.…”
Section: Introductionmentioning
confidence: 99%
“…Thostenson and Chou processed GFRPs with embedded CNTs in an epoxy matrix to evaluate the onset and evaluation of damage. [1,2,22] They showed that tracking direct current (DC) resistance changes during mechanical deformation is remarkably sensitive to the initial stage of matrix microcracking and could be used to identify the nature and progress of damage.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of numerous piezoresistive materials presently investigated for strain sensing and structural monitoring applications, most of them often demonstrate linear strain sensitivities with a few demonstrating a bilinear sensitivity in dynamic or monotonic load tests [33,34,42,[47][48][49][50][51][52][53][54]. In these studies, the researchers typically report the gage factor in these linear regions using a least-squares linear fit to identify the slope (thus the gage factor).…”
Section: Circuit Element Strain Response Fittingmentioning
confidence: 99%